Cellular responses in the respiratory tract following intranasal administration of Peste des petits ruminant vaccine in goats - Ezeasor, Chukwunonso Kenechukwu; Emikpe, Benjamin Obukowho; Mohd Yusoff, Sabri; Afusat, Jagun; Anosa, Victor O. (Sociedad Chilena de Anatomía, 2013)
A trial was conducted to compare the cellular responses in the respiratory tract in intranasal vaccination against caprine Peste des petits ruminant lineage 1 variant virus infection with intramuscular and subcutaneous vaccinations in order to elucidate the mechanism of the protection. Twenty four goats were divided into four equal groups. Group 1 was vaccinated intranasaly, group 2 was vaccinated subcutaneously, and group 3 intramuscularly, while Group 4 was the unvaccinated control group. In each group the vaccinations were carried out once. All goats were challenged intratrachealy with PPR virus at a concentration of 106.5 TCID50 two weeks after vaccination and were euthanised 21 days after the challenge. The bronchoalveolar lavage differential count, bronchial associated lymphoid tissue (BALT) responses were measured using standard techniques. Descriptive Statistics and ANOVA was employed and significance was at p < 0.05. The exposure also resulted into significant increase in the number and size of BALT as well as the number of lymphocytes in BALT. This study showed the mechanism of the protective effect of intranasal vaccination of PPR vaccine observed with the strong mucosal and defensive cellular responses in the respiratory tract observed than the subcutaneous and intramuscular routes.